Capital Expenditure Allocation Analysis Of Local Governments - Purwanto; Rizki Indrawan; Heryanti, Ajeng Nuraeni (International Journal of Science, Technology & Management, 2022)
Because of the resources limitation so resource allocation is a fundamental issue for public sector budgeting especially revenue and expenditure calculation. Regional budget distribution shows local government policies on development funding whereas capital expenditure is concerned with a component of direct expenditure of government budgets that deliver output in the form of fixed asset. This study purposes to determine factors that impress capital expenditure allocation of local governments, are Economic Growth and Regional Revenue (PAD). The population of this study is 35 local governments in the Province of Central Java, Indonesia. By employing multiple regression analysis, t and F test on secondary data from the 2015-2020 Budget Realization Reports of local governments in the Central Java Province, the result shows that economic growth and regional income partially and simultaneously have a positive effect on capital expenditure. These findings imply that local governments should look more carefully at managing their finances, have a strong desire, and provide capital for capital expenditures that have implications for the long-term welfare of local communities. The limitation of this research is that this research is carried out with a quantitative approach and to find out the real conditions in decision making on local government budgeting, it is recommended for further research to use a mixed quantitative and qualitative method.